Functional Characterization of Hexacorallia Phagocytic Cells - Snyder, Grace A.; Eliachar, Shir; Connelly, Michael T.; Talice, Shani; Hadad, Uzi; Gershoni-Yahalom, Orly; Browne, William E.; Palmer, Caroline V.; Rosental, Benyamin; Traylor-Knowles, Nikki (Frontiers in Immunology, 2021)
Phagocytosis is the cellular defense mechanism used to eliminate antigens derived from dysregulated or damaged cells, and microbial pathogens. Phagocytosis is therefore a pillar of innate immunity, whereby foreign particles are engulfed and degraded in lysolitic vesicles. In hexacorallians, phagocytic mechanisms are poorly understood, though putative anthozoan phagocytic cells (amoebocytes) have been identified histologically. We identify and characterize phagocytes from the coral Pocillopora damicornis and the sea anemone Nematostella vectensis. Using fluorescence-activated cell sorting and microscopy, we show that distinct populations of phagocytic cells engulf bacteria, fungal antigens, and beads. In addition to pathogenic antigens, we show that phagocytic cells engulf self, damaged cells. We show that target antigens localize to low pH phagolysosomes, and that degradation is occurring within them. Inhibiting actin filament rearrangement interferes with efficient particle phagocytosis but does not affect small molecule pinocytosis. We also demonstrate that cellular markers for lysolitic vesicles and reactive oxygen species (ROS) correlate with anthozoan phagocytes. These results establish a foundation for improving our understanding of hexacorallian immune cell biology.